Effect of Men Infertility on Serum Creatine ‎Kinase Activity ‎ (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
mThe present study was carried out on 60 patientsm with male factor infertility comparedmwith 60 healthy controls, their ages ranged betweenn20-56 years in Maternity and Childhood Teaching Hilla Hospital and in a biochemistry laboratory of Pharmacy college of Babylon university,  between Junem2014 – Junuary 2015. The purpose of this study is to investigate CK activity, serum creatine,mcreatinine levels and semen parametersmin infertile men only ,infertile with DM, smoking ifertile,nand hypertention with infertile patients. The present resultsbshowed a statistically significant deferences (p